A problem of thick circular plate in modified couple stress thermoelastic diffusion with phase-lags. Issue 3 (10th October 2016) - Kumar, Rajneesh; Devi, Shaloo; Sharma, Veena
Abstract : Purpose: The purpose of this paper is to investigate the two-dimensional axisymmetric problem in a homogeneous, isotropic modified couple stress thermoelastic diffusion (TD) medium in the context of dual-phase-lag model. Design/methodology/approach: The Laplace and Hankel transforms have been applied to find the general solution to the field equations. The components of displacement, stresses, temperature change and chemical potential are obtained in the transformed domain. The resulting quantities are obtained in the physical domain by using numerical inversion technique. Findings: The components of normal stress, tangential stress, tangential couple stress, temperature change and chemical potential are obtained numerically and depicted graphically to see the effect of dual-phase-lag diffusion (DLD), dual-phase-lag heat transfer (DLT) and TD models in the absence and presence of couple stress parameter. Originality/value: Comparisons are made in the absence and presence of couple stress DLD, DLT and TD models.